2021
DOI: 10.1016/j.biopsych.2020.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Examining Sex-Differentiated Genetic Effects Across Neuropsychiatric and Behavioral Traits

Abstract: BACKGROUND: The origin of sex differences in prevalence and presentation of neuropsychiatric and behavioral traits is largely unknown. Given established genetic contributions and correlations, we tested for a sex-differentiated genetic architecture within and between traits. METHODS: Using European ancestry genome-wide association summary statistics for 20 neuropsychiatric and behavioral traits, we tested for sex differences in single nucleotide polymorphism (SNP)-based heritability and genetic correlation (r … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 53 publications
5
54
0
Order By: Relevance
“…While this analysis was not significant in the NCMH data, the point estimate was actually higher in the early onset group analysis in NCMH [OR = 1.17(0.93–1.47)] compared to PGC [OR = 1.08(1.02–1.15)], indicating that the lower power of the smaller NCMH sample to detect such a small effect may have impacted on the lack of consistency in terms of statistical significance. This study also adds to other cross-disorder analyses of common genetic variants, which show moderate genetic correlations across ADHD, anxiety and depression, with no significant sex differences observed across these genetic correlations [ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…While this analysis was not significant in the NCMH data, the point estimate was actually higher in the early onset group analysis in NCMH [OR = 1.17(0.93–1.47)] compared to PGC [OR = 1.08(1.02–1.15)], indicating that the lower power of the smaller NCMH sample to detect such a small effect may have impacted on the lack of consistency in terms of statistical significance. This study also adds to other cross-disorder analyses of common genetic variants, which show moderate genetic correlations across ADHD, anxiety and depression, with no significant sex differences observed across these genetic correlations [ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 83%
“…Genome-wide association studies (GWAS) have identified robustly associated risk alleles for both disorders, accounting for 26% of variance in anxiety and 8.7% of variance in major depressive disorder (MDD) [ 10 , 11 ]. The genetic correlation between males and females is very high for each of these disorders and larger samples are needed to identify SNPs showing a genome-wide significant sex difference in allele frequency [ 12 , 13 ]. GWAS have also demonstrated that a significant proportion of the genetic liabilities of anxiety and MDD are shared with other psychiatric disorders in males and females [ 10 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the association between the PRS and worse cognitive performance in mid- and old age, as well as worse school performance was seen in males only with no trend effects in females, indicating sex-specific effects of schizophrenia genetics on cognitive ability in healthy individuals across the entire lifespan. Although it has been proposed that the impact of sex should be tested in genetic studies of schizophrenia given the significant differences in disease manifestation 5658 , to our knowledge, sex differences in the effect of schizophrenia PRS on cognition has only been considered in one previous study, where sex-stratified analyses showed that the effect of schizophrenia PRS on verbal memory and semantic fluency in older adults reached significance only in males 40 . Here, we were able to demonstrate a significant sex*PRS interaction thus demonstrating that there are statistically reliable differences in the effect of PRS between the sexes, and showed that this effect was not seen for a genetic score for general cognitive ability, but instead specific to schizophrenia genetics.…”
Section: Discussionmentioning
confidence: 99%
“…A schizophrenia GWAS stratified by sex did not reveal any genome-wide significant sex-specific associations 59 , but a genome-wide genotype-by-sex interaction analysis of risk for schizophrenia found genome-wide significant SNP-by-sex interactions 57 . However, no consistent sex differences in SNP-based heritability have been identified in schizophrenia 58 . Taken together, our results suggest that the effect of schizophrenia genetics on a certain disease endophenotype, cognitive ability, is sex-specific.…”
Section: Discussionmentioning
confidence: 99%